Advancing conceptualization and measurement of psychological capital as a collective construct. (June 2015) - Dawkins, Sarah; Martin, Angela; Scott, Jenn; Sanderson, Kristy
Psychological capital (PsyCap) has been conceptualized as an individual-level construct concerned with an employee's state of positive psychological development. However, research has now started to examine PsyCap as a collective phenomenon. Although positive associations between team-level PsyCap and team-level functioning have been demonstrated empirically, there has been limited synopsis regarding the theoretical and measurement foundations of PsyCap at higher levels of analysis. This conceptual article extends collective PsyCap scholarship by applying a multilevel-multireferent framework to explore alternate conceptualizations of collective PsyCap. The framework furthers understanding of PsyCap at higher levels by exploring unique antecedents and emergent processes relating to five proposed forms of collective PsyCap. A series of testable propositions pertaining to the antecedent network of collective PsyCap are offered to guide empirical multilevel PsyCap research.